ANALGESIC ACTIVITY OF HYDROALCOHOLIC EXTRACT OF AERIAL PARTS OF MALVASTRUM COROMANDELIANUM - Bhupesh CS; B, Rohit; D, Kalyani (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of this study is to explore the antinociceptive property of hydroalcoholic extract of Malvastrum coromandelianum. Pain is an unpleasant sensory and emotional experience associated with actual and potential tissue damage. Various types of pain are seen in humans, somatic, visceral, and neuropathic pain. M. coromandelianum belongs to Malvaceae family. Traditionally, it is used as an emollient, anti-inflammatory, analgesic, and antidysenteric. Methods: The antinociceptive effects of hydroalcoholic extract of M. coromandelianum (HEMC) were evaluated by tail-flick, hot-plate, and acetic acid induced writhing method. Rats were divided into four groups. The first group which served as control was administered with aqueous 1% tragacanth suspension. The second group received standard drug, morphine (5 mg/kg) orally as a suspension. Third and fourth group received HEMC (200 and 400 mg/kg) and served as test drug treatment group, 30 minutes after treatment the reaction time and number of writhes was noted. Results: HEMC produced significant antinociceptive effects against thermally induced pain. In tail-flick method, the peak effect of HEMC 400 mg/kg was shown at 60 minutes which is nearly equal to the peak effect of morphine 5 mg/kg. In hot-plate method, the HEMC showed significant analgesic effect up to 3 hrs after the treatment, whereas morphine showed significant effect up to 6 hrs. Conclusion: On the basis of finding, it may conclude that the HEMC shows its central analgesic action probably through inhibition of central pain receptors, whereas peripheral analgesic effect may be mediated by prostaglandin inhibition. Keywords: Pain, Analgesia, Hydroalcoholic extract of Malvastrum coromandelianum, Morphine.